Salt research with feeder lambs. - Hix, E.L.; Bell, T.D.; Parrish, D.B.; Good, A.L. (Kansas Agricultural Experiment Station, 2012)
The consumption of salt by herbivorous animals in general, and their apparent relish for salt, have been recognized for many years, but its importance may be questioned by many because of lack of knowledge of both the practical and fundamental aspects. It is commonly believed that the large amounts of potassium in feeds are antagonistic to the animal’s body sodium, and this potassium causes an excretion or loss of sodium which may be adequately replaced only by practical salt (NaCl) supplementation of the feed or ration. However, this belief has not been established conclusively in all of its elaborations designed to explain why these herbivorous animals require supplemental salt.
Keywords: Sheep; Salt; Performance; Feed digestibility